Tuyu wins Tiwi Islands Grand Final - Morris, Grey.
tag=1 data=Tuyu wins Tiwi Islands Grand Final tag=2 data=Morris, Grey tag=3 data=NT News tag=8 data=SPORTS tag=9 data=TIWI ISLANDS GRAND FINAL%TAPALINGA%TUYUTHURST ISLAND%SUPERSTARS tag=32 data=SINGH, NICK%HARRSION, LES%JACKSON, WAYNE%MARTIN, CLAIRE%AH KIT, JOHN tag=34 data=PRSS tag=61 data=25 tag=62 data=Mar tag=63 data=2002